Produksi Biogas Dari Limbah Kotoran Ayam Dan LimbahPasar Dengan Berbagai Konsentrasi Inokulum Dan LamaFermentasi - Nurjanah, Ida; , Dr. Siti Chalimah, M.pd (2016)
Biogas is one of the energy in the form of gasoline which is result from organics material. Biogas is one of the renewable energy. The materials that can be used for biogas production is vegetable waste, fruits waste, household waste, waste restaurant and livestock manure. One of the innovation materials that be used in the making of biogas is from the materials of waste market (vegetables and fruits) is mixed with chicken manure. The aim of this study is to know the result of biogas production with inokulum concentration of cow manure and long fermentation. The method that was used in this study is experiment method that used Rancangan Acak Lengkap (RAL) two factors. Factor one, is inoculums concentration (N) and factor 2 is duration fermentation. With six treatment and three times of repetition. The result of this study shows that inokulum concentration gave an impact in the result of quantity biogas production. However, the of duration fermentation there's no significance to word the result of quantity biogas production. The result of the highest quatity of biogas production in the inoculum consentration treatment cow manure 20% with the fermentation 20 days (N2S2) with the mean 172,33 ml. Meanwhile, the result of the lowest quantity bioga sin the inoculum consentration treatment cow manure is 10% with the fermentation 30 days (N1S3) with the mean 91,67 ml. The result of biogas experiment as quantitative with the roasting way in the bottle tonque there is no one which put outside the fire with the result that can be said that it haven't be formed of metan gasoline.